Cationic lipid emulsions containing heavy oils for the transfection of adherent cells - Yoo, HS; Kwon, SM; Kim, YJ; Chung, H; Kwon, IC; Kim, J; Jeong, SY (ELSEVIER, 2004)
A new cationic emulsion system with high density was prepared increasing in vitro transfection efficiencies of adherent cells. Lipiodol with a density of 1.3 (g/ml) was selected to increase the density of the DNA/emulsion complex. Cationic lipid emulsions were formulated with mixtures of lipiodol and squalene as the oil phase and 1,2-dioleoyl-sn-glycero-3-trimethylammonium-propane (DOTAP) as a cationic lipid. These emulsions were used to find the correlation between the density and the in vitro transfection efficiency. The physical characteristics of the new emulsion formulations were also determined. Heavier DNA/cationic lipid emulsion complex showed higher in vitro transfection efficiency on adherent cell lines in the presence of 10% serum compared to lighter ones. The cationic lipid emulsion formulated with lipiodol and DOTAP was more stable and showed better in vitro transfection efficiency than other carriers without lipiodol. Due to the high density of the carrier, the DNA/carrier complex sank to the bottom of the wells, thereby increasing the contact between the complex and adherent cells. The new lipiodol emulsion with high density showed superior transfection activities on adherent cells in the presence of serum. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: GENE-TRANSFER; DNA; COMPLEXES; EFFICIENT